Ecosystem Model Of Digital Tourism Candi Tebing Tegallinggah Gianyar - I Gusti Ketut Indra Pranata Darma; I Wayan Wiwin; Luh Putu Sri Ariati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This article explores the evolving landscape of the tourism industry in Bali, particularly in the context of digital technology. Denpasar city's digital tourism development, exemplified by the Kertalangu tourist village, showcases the integration of a website with various applications. The primary objective of rural tourism is to advance rural areas. In Gianyar Regency, Bedulu Village boasts a newfound tourist attraction – the Tegallinggah Cliff Temple, inaugurated at the end of 2019. However, the temple's potential remained largely untapped during the subsequent pandemic years due to the underutilization of digital tourism. The absence of a dedicated website and limited social media promotion hindered its visibility. Nevertheless, the limited reviews suggested a focus on quality over quantity. To address this, the researchers aim to create a digital ecosystem model for the Tegallinggah Cliff Temple, offering a structured and comprehensive approach for future tourist attractions in similar situations and locations.